A binding-induced sutured toehold activation for controllable DNA strand displacement reactions. Issue 14 (13th January 2015) - Zhu, Jing; Wang, Lei; Jiang, Wei
Abstract : Leveraging upon the environmental stimuli-responsive hairpin reconfiguration, a novel toehold activation strategy for controlling the DNA strand displacement was developed. Abstract : A novel toehold activation strategy was developed based on hairpin-reconfiguration which was initiated by the interaction between the hairpin and different environmental stimuli (Hg 2+ or ATP). Through variation of the concentration of environmental stimuli, it allowed the fine control of the DNA strand displacement rates almost 2 orders of magnitude.